Teisėjų tarybos konstitucinio statuso aspektų įžvalgos teismų finansavimo ir teisėjų atleidimo aktualijų kontekste - Šileikis, Egidijus (Vilnius University Open Series, 2024)
The constitutional consolidation and formal doctrinal development of the framework for the status of the Judicial Council in Lithuania is a reflection of the phenomena of the constitutional legal technique and the doctrinal activism of the Constitutional Court. No other institution referred to in the 1992 Constitution of Lithuania is so constitutionally abstract and so detailed in the doctrine of the Constitutional Court as the Judicial Council. The detail of the official concept of its composition, i.e. constitutionally justifiable (possible) and non-justifiable (impossible) members, which rejects the concept of a broader (politically inclusive) composition of the analogous institution referred to in Poland’s Constitution of 1997, can be viewed in a controversial way. This is important in relation to the aspects of a much more efficient coordination and consideration of the financing of the judiciary for the next year than is currently the case, as envisaged in the draft State budget law prepared by the Ministry of Finance and submitted by the Government to the Parliament (the Seimas). Such a draft, with the participation of the democratically empowered judges who guarantee the self-governance of the judiciary, could and should be more effectively coordinated and debated, and not in the Ministry of Finance or in the Government, but rather in the new Judicial Funding Council (or a differently named additional institution for the financial self-regulation of the judiciary) whose members would include not only judges, but also the relevant State politicians and civil servants (in particular, the Minister of Finance along with the Vice-Minister, and the chairpersons of at least two relevant committees of the Seimas), who, unfortunately, are constitutionally not allowed to be members of the Judicial Council under the Constitutional Court’s controversial strict (hard) jurisprudence in any situation.